Issues of Designing Effective Educational Programs in the Field of “Applied Informatics” in the Conditions of Innovative Development - Yu. F. Telnov; M. S. Gasparian; M. A. Filyuk (Открытое образование (Москва))
The ever-growing demand for digital IT industry specialists brings to the fore the task of developing effective educational programs that ensure a high qualification level of graduates. The result of such activities – the turn-out of highly qualified specialists will depend on how much more detailed all the components of the educational activities of the University are considered, designed and implemented. Therefore, when developing and updating educational programs, higher education institutions will have to clarify the composition of professional competencies that must meet both the needs for effective performance of generalized labor functions and labor functions fixed in professional standards, and many educational parameters fixed in the regulatory framework of Russian higher education. The purpose of this research is to develop innovative educational programs at the stage of digital transformation of higher education and the transition to practice-oriented project training of University graduates in IT areas. The research tasks include the following stages: 1. Development of a conceptual model of an intelligent integrated educational environment based on the interface of ontologies of professional and educational standards. 2. Systematization and organization of elements of the digital repository and on its basis, the development of algorithms for generating educational-methodical and organizational-administrative content of the intellectual integrated educational environment. 3. Testing methods for generating content in the intelligent integrated educational environment. This task can be achieved only by integrating all components of the educational process into a single information and educational space. The solution to this problem is seen in the development of methods and tools for generating educational-methodical and organizational-administrative content based on the digital repository of the electronic learning system through knowledge management technologies that ensure the adaptability of the educational process using the ontological approach. Such work is currently being carried out at Plekhanov Russian University of Economics, including ICT areas. The analysis of professional activity of graduates of bachelor’s degree and master’s degree programs in terms of requirements of the Federal State Education Standards of Higher Education in the field of “Applied Informatics” has shown that these requirements with varying degrees of completeness correspond to a number of professional standards in the field of IT industry. As a result of the analysis of the factors for improving the quality of the educational process, the ways to improve training of bachelors in the field of “Applied Informatics” in the context of combining ontologies of professional and educational standards are outlined. The article also provides approaches to the development of an approximate basic educational program in this direction and reveals the method of its engineering, based on the interaction and composition of elements of the integrated information and educational space and, on its basis, semantic modeling and automatic generation of educational and organizational and managerial content. Thus, the proposed method will contribute to improving the efficiency of the educational process and meet the world trends in the development of science in this field of knowledge, which will bring the training of highly qualified IT industry specialists to a qualitatively new level.